Avaliação da influência de marcadores genéticos, laboratoriais e clínicos na ocorrência de doença cerebrovascular em crianças com anemia falciforme triadas pelo programa de triagem neonatal de Minas Gerais e acompanhadas no hemocentro de Belo Horizonte da fundação hemominas - Andre Rolim Belisario (2015)
Cerebrovascular disease (CVD) is a severe complication associated with sickle cell anemia (SCA). Abnormal transcranial Doppler (TCD) identifies some children at high risk, but other markers would be helpful. Objectives: This cohort study was aimed at evaluating the effectsof clinical, laboratorial, and molecular biomarkers on the risk of developing CVD in children from Minas Gerais, Brazil. A secondary aim was to identify the -thal mutations causing S- thalassemia in the newborn cohort of Minas Gerais state. Methods: Outcomes studied wereovert ischemic stroke, and high-risk TCD. Possible genetic markers were genotyped by PCR/RFLP. Clinical and hematological data were retrieved from childrens records. The quantitative determination of glucose-6-phosphate dehydrogenase (G6PD) activity wasperformed using an enzymatic colorimetric assay. The molecular analysis of HBB was performed by DNA sequencing. Results: Out of 440 children, 395 (89.8%) had Hb SS genotype, 28 (6.4%) had Hb S0-thal, 13 (3%) had Hb S/hereditary persistency of fetal hemoglobin (HPFH), and four (0,9%) Hb S+-thal. In Hb SS children, the cumulative incidence of clinical ischemic stroke by 8.0 years of age was 7.4% (95% CI, 4.6610.14%) and that of high-risk TCD by 11.5 years of age was 14.2% (95% CI, 8.9119.49%). Paper 1: No effect of VCAM-1 c.1238G>C single nucleotide polymorphism (SNP) on stroke or CVD risks was detected. Cumulative incidence of stroke was significantly higher for children withTNF- -308A allele (p=0.02) and lower for children with HBA deletion (p=0.02). However, no association between CVD and TNF- -308G>A was found. CVD cumulative incidence was significantly lower for children with HBA deletion (p=0.004). Paper 2: The frequency of stroke was null (0/83) for children who harbored the ENPP1 KK genotype, 6.8% (7/103) for those with QQ genotype, and 7.7% (16/209) for children with KQ genotype (P=0.037). The cumulative probability of stroke was significantly (P=0.015) higher for children with the QQ genotype than for those with the KK genotype. Similar results were obtained comparing QQ/KQ genotypes as one group with the KK group. No association between GOLGB1Y1212C or PON1 Q192R and stroke or stroke risk was detected. Paper 3: The final multivariate model for stroke risk included high white blood cell count and reticulocyte count, acute chest syndrome rate, and the single nucleotide polymorphisms (SNPs) TEK rs489347 and TNF- rs1800629. The model for high-risk TCD included high reticulocyte count and theSNPs TEK rs489347 and TGFBR3 rs284875. Paper 4: The prevalence of molecularly-defined deficiency was 4.3% (95%CI: 2.3%6.3%). The mean G6PD activity was 16.88 U/g Hb [standard error of the mean (SEM) 0.28] in the group without G6PD molecular deficiency and 8.43 (SEM 1.01) U/g Hb in the group with G6PD A molecular deficiency. G6PD moleculardeficiency was not associated with any hematological features. No effects of G6PD molecular deficiency on clinical ischemic stroke or high-risk TCD were detected. The mean G6PD activity was similar in children who had clinical ischemic stroke and in those without stroke. Similar results were obtained in analyses comparing children who had high-risk TCD and those without high-risk TCD. Paper 5: Thirteen children were included, nine (69.2%) had the Hb S/HPFH deletion type 2, and four (30.8%) had deletion type 1; eleven children (84.6%) were /, and two (15.4%) /-3.7. The mean concentration of total hemoglobin (Hb) andHb F was 12.52 ± 0.56 g/dl and 42.31% ± 1.97%, respectively. All children were classified as having low-risk transcranial Doppler. Paper 6: Analysis of IL-10 haplotype in our cohort showed that 99 (25.1%) children were GCC/ATA, 85 (21.5%) ACC/ATA, GCC/ACC 79 (20%), GCC/GCC 50 (12.7%) ATA/ATA 47 (11.9%), ACC/ACC 34 (8.6%), and one (0.3%)child presented an uncommon haplotype (GCC/GTA). There was no significant difference in the frequencies of SNPs in the promoter region of IL-10 gene between children with and without stroke or high-risk TCD. Likewise, no association was observed between IL-10 xihaplotypes and stroke or high-risk TCD. Paper 7: Out of 54 S-thal children, 14 (25.9%) children had the codon 39 (C>T) mutation, 12 (22.2%) had IVS-I-1 (G>A), eight (14.8%) had IVS-I-6 (T>C), five (9.3%) had -29 (A>G TATA box), three (5.6%) had IVS-II-1 (G>A), three (5.6%) had IVS-I-110 (G>A), two (3.7%) had -92 (C>T), two (3.7%) had IVS-II-844(C>A) and IVS-II-839 (T>C) in cis mutations, two (3.7%) had IVS-I-5 (G>A), one (1.9%) had -88 (C>T), one (1.9%) had poly A signal (T>C), and one child (1.9%) had IVS-I-2 (T>C) mutation. Paper 8: Two children had a 92 (C>T) mutation and two had IVS-II-844 (C>A) plus IVS-II-839 (T>C) in cis mutations. The mean hemoglobin concentration was 12.0±0.7g/dL and the mean hemoglobin A concentration was 40.4±1.1%. All the children were clinically oligosymptomatic and none of them had complications attributable to sickle cell disease. The 92 (C>T) and IVS-II-844 (C>A)/IVS-II-839 (T>C) mutations associated with the S allele lead to a silent form of S+-thal. Conclusions: Our study identified clinical, laboratorial, and molecular risk factors for stroke and CVD development in children from the Minas Gerais state SCA newborn cohort, Brazil. The Minas Gerais state is the second most heterogeneous state in Brazil in terms of -thal mutations and has a relatively different molecular pattern when compared to other Brazilian regions.